Satellite Monitoring of Anomalous Wildfires in Australia - Bondur, Valery G.; Gordo, Kristina A.; Voronova, Olga S.; Zima, Alla L. (Frontiers in Earth Science, 2021)
Here we present the results of satellite monitoring of wildfires in Australia for the period of 2001–2020. Annual and monthly dynamics of wildfire areas and CO and CO2 carbon-bearing trace gas emissions from wildfires have been analyzed for the whole territory of Australia based on satellite data. It was found that anomalous fires occurred in the territory of New South Wales during the 2019–2020 fire season. Values of burned-out areas exceeded the values of previous years 3.5–25.8-fold. Annual mean volumes of carbon-bearing gas emissions in this region exceeded the values of previous years 4–59-fold for carbon monoxide CO and 4.6–50-fold for carbon dioxide CO2. The spatial distribution of the excess concentrations of CO from wildfires in New South Wales was recorded according to the monthly mean data of the AIRS instrument (Aqua satellite). At the same time, the excess of CO2 concentration in the atmosphere was estimated using the TANSO-FTS (GOSAT satellite) data. It was demonstrated that an anomalously high number of fires in this state of Australia was caused by extreme drought associated with abnormally high surface temperatures, low rainfall and humidity which created conditions for intense fires and emissions of carbon-bearing gases associated with the combustion of eucalyptus and tropical rain forests prevailing in this region.